Can road user delays at urban railway level crossings be reduced? Evaluation of potential treatments through traffic simulation. Issue 3 (September 2020) - Larue, Grégoire S.; Miska, Marc; Qian, Gongbin; Wullems, Christian; Rodwell, David; Chung, Edward; Rakotonirainy, Andry
Highlights: Increased road and rail traffic result in congestion at railway level crossings. Level crossing congestion increases significantly road users' travel time. A range of technology treatment were evaluated with traffic simulation. Treatments reducing the gap between estimated and actual train arrival at a crossing are the most beneficial. Abstract: Railway level crossing closures can disrupt traffic flow significantly, especially in peak hours. The current increases in road and rail traffic worsen the situation and can result in congestion known to significantly increase road users' travel times. In this study, seven of the most problematic level crossings around Brisbane, Australia, were surveyed. The effectiveness of a set of treatments was tested and discussed using computer simulation models. The study found that the variability of warning times is the major cause of unnecessary boom gate downtime. Our observations showed that warning times could be reduced by 10–40 s on average for each crossing activation at the investigated sites. A major cause for the variability in warning times are trains stopping at stations that are not equipped with express train identification, and actual train speeds being lower than posted line speeds. Various tested treatments were found to be effective at reducing level crossing closure duration and reducing the variability in warning times, resulting in travel times reducing by 7–57% for road users, depending on the level crossing considered. This study shows the potential for the short to medium-term treatment of congestion issues at active level crossings, which are necessary with the current increased rail and road traffic flows.